CHILDFREE AND THE POSITION OF CHILDREN FROM AN ISLAMIC PERSPECTIVE IN INDONESIA - Semaun Al Usman; Maksudin Maksudin; Nurhadi Nurhadi; Thonthowi Thonthowi; Muhammad Alfreda Daib Insan Labib (Hukum Islam, 2023)
Having children is the hope of every couple, children are the dream of the couple themselves, because children are very important in the sustainability of life. This is because children have important roles and positions, both in family and community life, and children are the next generation of a generation. Some cases in this country make some people have a special view in understanding the meaning of Childfree. The method in this study uses descriptive qualitative, this research is certainly present as a response to the phenomena that are around. With a phenomenological approach, researchers try to capture various problems that exist in society and reveal the meaning contained in them. This study explains that in the context of human life, humans will be faced with two elements of life, namely personal affairs (personality) and environmental or social affairs (Society), and these two elements are interconnected, and there needs to be communal agreement about social life. In marriage, it is human nature to run a home life, and the fulfillment of the fiitrah of a household is to have children.